2019
DOI: 10.1016/j.ijmultiphaseflow.2019.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Structured planar laser-induced fluorescence (S-PLIF) for the accurate identification of interfaces in multiphase flows

Abstract: Annular flows are employed in numerous engineering and industrial processes relating to the chemical, oil and gas, solar and nuclear energy industries. Yet, the reliable time-and space-resolved measurement of film thickness in these flows still eludes us, as the moving and wavy interface renders the application of optical diagnostics, such as planar laser-induced fluorescence (PLIF), particularly challenging. In this research article, we present a novel adaptation of PLIF, which we refer to as structured PLIF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 49 publications
0
36
0
Order By: Relevance
“…These techniques are employed to overcome some important problems identified in the literature and early-stage experimental trials with planar laser-induced fluorescence (PLIF). It was found that temperature-driven gradients led to local refractive index variations that ultimately resulted in light distortion, which prevented locating the interface accurately [26,28,39,40]. PLIF measurements were also unsuitable due to reflections induced by the ice layer, hence lowering the accuracy of the ice layer tracking.…”
Section: Laser Diagnosticsmentioning
confidence: 99%
“…These techniques are employed to overcome some important problems identified in the literature and early-stage experimental trials with planar laser-induced fluorescence (PLIF). It was found that temperature-driven gradients led to local refractive index variations that ultimately resulted in light distortion, which prevented locating the interface accurately [26,28,39,40]. PLIF measurements were also unsuitable due to reflections induced by the ice layer, hence lowering the accuracy of the ice layer tracking.…”
Section: Laser Diagnosticsmentioning
confidence: 99%
“…Details of the previous experimental campaigns performed in this facility can be found in Refs. [11,13,14,17]. The test-section consists of a vertical ∼ 5 m long fluorinated ethylene propylene (FEP) pipe of radius, R = 16.2 ± 0.2 mm.…”
Section: Flow Facilitymentioning
confidence: 99%
“…Häber et al [12] performed ray-tracing simulations, and revealed an overestimation in PLIF-derived instantaneous film-thickness measurement of up to 30% (in PLIF90), primarily caused by total internal reflection and refraction effects about the gas-liquid interface. Nevertheless, as discussed in the study by Charogiannis et al [13], PLIF90 measurements are also prone to a second source of error, associated with the imaging angle used, resulting in underestimation of the film thickness. Interestingly, the two errors were found to be of same order, but with opposite effects, which almost cancelled each other out during the time-averaging process in falling films (resulting in measurements close to theoretical predictions).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…PLIF is a two-dimensional (2-D) planar technique used to extract information on the distribution of the phases and interface profiles, but also in other flows on scalar fields (e.g., Markides et al, 2016), while PIV/PTV can provide information on 2-D velocity vector-fields, conventionally in flow crosssections, but also over interfaces between immiscible phases (e.g., Charogiannis et al, 2016). In two-phase isothermal flows, PLIF has been used in falling-film flows (Charogiannis et al, 2015;2017a,b;, in gas-liquid annular vertical flows (Schubring et al, 2010;Zadrazil et al, 2014a,b;Charogiannis et al, 2019;Cherdantsev et al, 2018;, co-current liquid-liquid downward vertical flows (Liu et al, 2006), and co-current liquid-liquid horizontal flows (Morgan et al, 2012;2013), by employing a thin laser-sheet to illuminate a plane through the flow of interest. The addition of a fluorescence dye in one of the fluid phases enables the spatial identification of the seeded phase.…”
Section: Introductionmentioning
confidence: 99%